Effects of a Maximal Energy Scale in Thermodynamics for Photon Gas and Construction of Path Integral - Das, S.; Pramanik, S.; Ghosh, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
In this article, we discuss some well-known theoretical models where an observer-independent energy scale or a length scale is present. The presence of this invariant scale necessarily deforms the Lorentz symmetry. We study different aspects and features of such theories about how modifications arise due to this cutoff scale. First we study the formulation of energy-momentum tensor for a perfect fluid in doubly special relativity (DSR), where an energy scale is present. Then we go on to study modifications in thermodynamic properties of photon gas in DSR. Finally we discuss some models with generalized uncertainty principle (GUP).